AMYLOIDOSIS HEART IN ELDERLY - L. I. Dvoretsky; O. Yu. Karpova; E. N. Alexandrova; S. Yu. Petrova (SINAPS LLC, 2015)
The data on the incidence, clinical presentation, diagnostic methods amyloidosis of the heart in different types of amyloidosis. The features of the current heart amyloidosis, highlights the difficulty of diagnosis and differential diagnosis in the elderly. As an illustration, describes a clinical case of amyloidosis of the heart in 83-year-old patient, the main manifestation of which was congestive heart failure.